TANTANGAN PENGGUNAAN MEDIA BARU UNTUK MEMBANGUN KARAKTER ISLAMI ANAK MUSLIM GENERASI ALPHA - Putri Amalia; Ade Irma (Jurnal Komunikasi dan Media, 2026)
This article examines the structural challenges of new media use among Muslim Alpha Generation children in Indonesia from an Islamic character education perspective. Alpha Generation, born after 2010 and raised entirely in a digital ecosystem, represents the most exposed yet most vulnerable cohort in Indonesia's digital landscape regarding Islamic character formation. Using a systematic literature review method that integrates Islamic character education theory, generational communication theory, digital literacy frameworks, and empirical findings on Alpha Generation's religious attitude formation, this study analyzes four interconnected dimensions of challenge: (1) the structural dominance of algorithmic agendas that displace Islamic values in children's content consumption; (2) multidimensional digital literacy deficits that hinder critical engagement with religious information on social media; (3) the weakening of family-based Islamic socialization amid digital distraction; and (4) the gap between the potential of digital media for Islamic education and its actual utilization. The article argues that effective solutions require an integrated tripartite architecture involving family, Islamic educational institutions (pesantren and madrasah), and community, positioned not as supplementary but as foundational infrastructure for Islamic character development. Findings from referenced studies confirm that structured digital accompaniment programs, parental digital literacy strengthening, and Islamic-values-integrated curricula produce measurable improvements in children's positive media behavior and religious attitude formation.